2018
DOI: 10.1038/s41437-018-0075-0
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the BLUP alphabet for genomic prediction adaptable to the genetic architectures of complex traits

Abstract: Improvement of statistical methods is crucial for realizing the potential of increasingly dense genetic markers. Bayesian methods treat all markers as random effects, exhibit an advantage on dense markers, and offer the flexibility of using different priors. In contrast, genomic best linear unbiased prediction (gBLUP) is superior in computing speed, but only superior in prediction accuracy for extremely complex traits. Currently, the existing variety in the BLUP method is insufficient for adapting to new seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
71
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(72 citation statements)
references
References 55 publications
1
71
0
Order By: Relevance
“…Bayesian LASSO (Least Absolute Shrinkage and Selection Operator; PLOS ONE | https://doi.org/10.1371/journal.pone.0228724 February 7, 2020 1 / 15 a1111111111 a1111111111 a1111111111 a1111111111 a1111111111 [5]), BayesA, BayesB [4], RKHS (Reproducing Kernel Hilbert Spaces; [6]), and genomic BLUP [7] are examples of the most notorious. Additionally, further adaptations have been proposed to principal methods such as compressed BLUP, SUPER BLUP [8], and GP with higher-effect markers differentially modeled (e.g., as fixed effects; [3,9,10]). Simulations and empirical studies have shown that the ability of GP to associate phenotypic patterns to genomic variations is intrinsically related to the genetic architecture of traits [4,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Bayesian LASSO (Least Absolute Shrinkage and Selection Operator; PLOS ONE | https://doi.org/10.1371/journal.pone.0228724 February 7, 2020 1 / 15 a1111111111 a1111111111 a1111111111 a1111111111 a1111111111 [5]), BayesA, BayesB [4], RKHS (Reproducing Kernel Hilbert Spaces; [6]), and genomic BLUP [7] are examples of the most notorious. Additionally, further adaptations have been proposed to principal methods such as compressed BLUP, SUPER BLUP [8], and GP with higher-effect markers differentially modeled (e.g., as fixed effects; [3,9,10]). Simulations and empirical studies have shown that the ability of GP to associate phenotypic patterns to genomic variations is intrinsically related to the genetic architecture of traits [4,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Concerning additive models, genomic best linear unbiased prediction (GBLUP, Meuwissen et al, 2001;VanRaden, 2007) is a widely-used linear mixed model (Da et al, 2014;RönnegĂ„rd and Shen, 2016;Covarrubias-Pazaran et al, 2018). The computational steps involved in GBLUP are much faster than Bayesian methods and it has been difficult to find a method which consistently outperforms GBLUP when predicting complex traits (Wang et al, 2018). Daetwyler et al (2010) showed that BayesB can yield higher accuracy than GBLUP for traits controlled by a small number of quantitative trait nucleotides, emphasizing that the genetic architecture of the trait has an important impact on which method may predict better (Wimmer et al, 2013;Momen et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, genetic diversity within the TR is fundamental for estimating marker effects appropriately (Norman et al, 2018). Finally, the region in the genome where individuals are more similar also affects genomic predictions, especially for oligogenic traits (Zhang et al, 2010;Wang et al, 2018). Some strategies have been designed to weight genetic relationship matrices on the basis of their marker effects regardless of their position or linkage disequilibrium [trait-specific relationship matrix best linear unbiased prediction (taBLUP)] (Zhang et al, 2010), or weighting only bin-selected quantitative trait nucleotides [super best linear unbiased prediction (sBLUP)] (Wang et al, 2014).…”
mentioning
confidence: 99%